Pengaruh leverage, ukuran perusahaan, dan profitabilitas terhadap kualitas laba - Nirmalasari, Febriyana; Wahyu Widati, Listyorini Wahyu Widati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Earnings quality is the quality of earnings information available to the public that is able to show the extent to which earnings can influence decision making and can be used by investors to assess the company. The quality of earnings in a financial report is very important, because if the quality of the company’s earning is low, it shows actual information about management performance in that period. If the company’s profits increase, the profits contained in the company’s financial statements cause managers to take various ways to prepare financial statements as effectively as possible for both internal and external parties. This study aims to analyze and examine the effect of leverage, firm size, and profitability on earnings quality. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period with a total sampel of 380 companies. The sampling method used in this research is purposive sampling. The data analysis techique used in this study in multiple regression analysis and using the SPSS 24 program. The results of the research conducted state that leverage has a significant negative effect on earnings quality, firm size has no effect on earnings quality, and profitability has a significant positive effect on earnings quality.